Cultural integration of first-generation immigrants: Evidence from European Union countries - Eleftherios Giovanis; Sacit Hadi Akdede (Review of Economic Analysis (REA), 2023)
In this study, we aim to explore and compare the frequency of attendance and the reasons for non-attendance to cultural activities between natives and first-generation immigrants in thirteen European countries. The empirical analysis relies on data from the special module on cultural participation in the European Union-Income and Living Conditions Survey (EU-SILC) in 2015. We apply the Probit and multinomial Probit models. This study contributes to the literature by exploring the determinants of cultural participation and comparing the frequency of participation in cultural activities between natives and first-generation immigrants. Furthermore, the study explores the reasons for non-participation in cultural activities, highlighting potential differences between countries and between the European Union (EU) and non-EU migrants. The results highlight that social interactions depend on several factors related mainly to the country of destination and employment opportunities and individual factors related to the migrant, including demographic and economic characteristics and the length of residence in the host country. The findings show that the length of residence of immigrants in the host countries is positively correlated with a higher frequency of attendance, indicating that cultural participation can be, by its nature, a long-term process or 'experienced' activity. The findings also show that in most cases, migrants do not attend the cultural activities we explore because of financial constraints and not due to lack of interest. Thus, this highlights that the economic integration of migrants could be the primary driver of cultural participation and integration.
Keywords: F22; J15; Z10; 330; Cultural Integration; Discrete Choice Models; First-Generation Immigrants; International Migration; Integration; Multiculturalism